How Does the Fusion of Sensory Information From Audition and Vision Impact Collective Behavior? - Roy, Subhradeep; Lemus, Jeremy (Frontiers in Applied Mathematics and Statistics, 2021)
This study investigates how combined information from audition and vision impacts group-level behavior. We consider a modification to the original Vicsek model that allows individuals to use auditory and visual sensing modalities to gather information from neighbors in order to update their heading directions. Moreover, in this model, the information from visual and auditory cues can be weighed differently. In a simulation study, we examine the sensitivity of the emergent group-level behavior to the weights that are assigned to each sense modality in this weighted composite model. Our findings suggest combining sensory cues may play an important role in the collective behavior and results from the composite model indicate that the group-level features from pure audition predominate.